An Experimental Study on Improving Grindability with LN2 Coolant for Grinding AISI D2 Tool Steel - Sharma A.; Chaudhari A.; Yusufzai M.Z.K.; Vashista M. (My University, 2025)
In today’s modern manufacturing era, it is critical to have an environmentally friendly machining system. This research introduced a novel approach with a developed setup for applying liquid nitrogen (LN2) cryogen in cryogenic machining as an environmental concern. In order to facilitate meaningful comparisons, grinding experiments were carried out in three distinct environments: dry, wet, and cryogenic cooling. The experimental results revealed that compared to dry and wet cooling, cryogenic cooling is beneficial in lowering the grinding force (54-64% and 38-45% in Ft, 44-55% and 31-35% in Fn), reducing the temperature (64-69% and 50-56%), improving the surface finish, causing less damage to the surface condition, and forming C-type or semicircular chips. Also, the influences of different process parameters, which include table feed rate and cryogen pressure, on surface characteristics of AISI D2 tool steel while employing surface functional indices, namely, surface bearing index (Sbi) and core fluid retention index (Sci), were investigated. Outcomes showed that the Sbi and Sci values in cryogenic grinding were greater than those of dry and wet grinding under the same conditions. It was clearly observed that the results of Sbi and Sci under cryogenic cooling indicated better surface characteristics over the bearing characteristics and fluid retention properties of the ground sample. © 2023, ASM International.